Study protocol for investigating the performance of an automated blood test measuring GFAP and UCH-L1 in a prospective observational cohort of patients with mild traumatic brain injury: European BRAINI study. Issue 2 (25th February 2021) - Richard, Marion; Lagares, Alfonso; Bondanese, Victor; de la Cruz, Javier; Mejan, Odile; Pavlov, Vladislav; Payen, Jean-François
Abstract : Introduction: Mild traumatic brain injury (mTBI) is a common cause of clinical consultation in the emergency department. Patients with mTBI may undergo brain CT scans based on clinical criteria. However, the proportion of patients with brain lesions on CT is very low. Two serum biomarkers, glial fibrillar acidic protein (GFAP) and ubiquitin carboxy-terminal hydrolase L1 (UCH-L1), have been shown to discriminate patients regarding the presence or absence of brain lesions on initial CT scan when assessed within the first 12 hours after TBI. However, the current technique for measuring serum concentrations of GFAP and UCH-L1 is manual and time consuming, which may hinder its use in routine clinical practice. This study assesses the diagnostic accuracy of an automated assay for the measurement of serum GFAP and UCH-L1 in a cohort of patients with mTBI who received a CT scan as the standard of care. Methods and analysis: This is a prospective multicentre observational study of 1760 patients with mTBI recruited in France and Spain across 16 participating sites. Adult patients with an initial Glasgow Coma Scale score of 13–15 and a brain CT scan underwent blood sampling within 12 hours after TBI. The primary outcome measure is the diagnostic performance of an automated assay measuring serum concentrations of GFAP and UCH-L1 for discriminating between patients with positive and negative findings on brain CT-scans. Secondary outcome measures include the performance of these two biomarkers in predicting the neurological status and quality of life at 1 week and 3 months after the trauma. Ethics and dissemination: Ethics approval was obtained by the Institutional Review Board of Sud-Ouest Outre Mer III in France (Re#2019-A01525-52) and Hospital 12 de Octubre in Spain (Re#19/322). The results will be presented at scientific meetings and published in peer-reviewed publications. Trial registration number: ClinicalTrials.gov: NCT04032509 .